Animal model considerations for chordoma research: reproducing the tumor microenvironment in vivo with humanized mice - Campilan, Beatrice; Schroeder, Christian; Sagaityte, Emilija; Arditi, Jonathan; Leary, Owen P.; Gokaslan, Ziya L.; Sullivan, Patricia L. Zadnik; Martinez-Moreno, Margot (Frontiers in Oncology, 2024)
Animal models have been commonly used in immunotherapy research to study the cell response to external agents and to assess the effectiveness and safety of new therapies. Over the past few decades, immunocompromised (also called immunodeficient) mice allowed researchers to grow human tumor cells without the impact of the host’s immune system. However, while this model is very valuable to understand the tumor biology and to understand the underlying mechanism of immunotherapy, the results may not always directly translate to humans. The tumor microenvironment has significant implications for tumor engraftment, growth, invasion, etc., and the immune system plays a critical role in shaping the tumor microenvironment. Human immunocompetent mice, also named humanized mice, are engineered mice that possess functional human immune cells. This in vivo model can be used to effectively study the effect of the human immune system to a human implanted tumor. Moreover, this can effectively mimic the response to treatment. This section is an overview of the current understanding of the different humanized mice that could be utilized to mimic the tumor microenvironment in chordoma.